872 Neoadjuvant chemoradiotherapy enhances T cell infiltration in pancreatic ductal adenocarcinoma but high percentage of regulatory T cells associates with poor survival. (9th November 2020) - Fullerton, Benjamin; Gartrell, Robyn; Enzler, Thomas; Kim, Pan; Fazlollahi, Ladan; Chen, Andrew; Perni, Subha; Weisberg, Stuart; Rizk, Emanuelle; Oh, Eun Jeong; Guo, Xinzheng; Chiuzan, Codruta; et al.
Abstract : Background: Currently, diagnosis with pancreatic ductal adenocarcinoma (PDAC) renders an almost intrinsically poor patient prognosis. Despite complete surgical resection and intense neoadjuvant and/or adjuvant treatment the great majority of patients will ultimately relapse and die from the disease. Further, PDAC has been characterized as highly immune resistant. It is speculated that radiation, chemotherapy, or chemoradiation cause the release of tumor antigens and inflammatory cytokines eventually leading to increased immunogenicity of PDAC. Methods: We used computational quantitative multiplex immune fluorescence (qmIF) (n=31) and the NanoString assay (n=34) to quantitatively analyze the effect of neoadjuvant chemoradiation (CRT) on the tumor immune microenvironment (TIME) of PDAC. Results: When comparing non-treated (NT) to neoadjuvant chemoradiation (CRT) tumors, the proportion of tumor within the overall tissue sample was markedly lower in treated tumors (figure 1; Mann Whitney U, U=25, p<0.0001). Additionally, the overall density of Ki67+ cells throughout all tissue was significantly lower in samples that received CRT (figure 1; Mann Whitney U, U=52, p=0.0067). An overall influx of CD3+ cells was noted in CRT samples. T cell influx was accompanied by upregulation of inflammatory genes. When considering T cell subsets, an increase in the CD8+ (Cytotoxic) and CD4+FOXP3+ (Treg) cell densities in the tumor of CRT samples was found. CD4+FOXP3- (T helper) cell density was found to be increased in the tumor, stroma, and overall tissue in CRT samples (figure 2). When comparing samples from patients who lived longer than 2 years to samples from patients who did not within the CRT group, a notably higher ratio of Tregs to CD3+ cells was observed in patients who lived less than 2 years (Mann Whitney U, U=0, p=0.0006). When used as a predictor, the ratio of Tregs to CD3+ cells also correlated closely to patient survival (figure 3); Mantel-Cox, p=0.0121). Conclusions: We find that CRT greatly alters the TIME of PDAC, altering distributions of tumor cells within the microenvironment and inducing an overall influx of T cells, including cytotoxic, helper, and Treg T cell subsets. In patients receiving CRT, it appears as though the proportion of T cells infiltrating the tumor that are Tregs is closely associated with patient outcome, with a higher proportion of Treg infiltration correlating with a poor outcome. This data suggests that therapies targeting regulatory T cells should be explored in combination with chemo-radiotherapy in PDAC. Ethics Approval: The study was approved by Columbia University's Ethics Board, approval number AAAQ7337.